Bombay lectures on highest weight representations of infinite dimensional lie algebras - Kac, Victor G., 1943-; Raina, A. K.; Rozhkovskaya, Natasha (Advanced series in mathematical physics ;, 2013)
The first edition of this book is a collection of a series of lectures given by Professor Victor Kac at the TIFR, Mumbai, India in December 1985 and January 1986. These lectures focus on the idea of a highest weight representation, which goes through four different incarnations. The first is the canonical commutation relations of the infinite dimensional Heisenberg Algebra (= oscillator algebra). The second is the highest weight representations of the Lie algebra gl 8 of infinite matrices, along with their applications to the theory of soliton equations, discovered by Sato and Date, Jimbo, Kas.